Influência da hidroterapia sobre a função pulmonar, força muscular respiratória e mobilidade tóracoabdominal em mulheres com síndrome fibromiálgica - Forti, Meire (2015)
The fibromyalgia syndrome (FMS) is a rheumatologic condition characterized by non-inflammatory widespread chronic pain and tender points in specific anatomic locations. In addition to the pain symptoms, FMS is also associated with the presence of a variety of symptoms such as fatigue and dyspnea, which has called attention to the review of the respiratory system in women with FMS. Thus, this work consisted of two studies aiming to elucidate the unknown aspects related to the respiratory system of women with FMS. The Study I, entitled "Pulmonary function, respiratory muscle strength and thoracoabdominal mobility in women with fibromyalgia syndrome: association with clinical manifestations", aimed to evaluate lung function, respiratory muscle strength and thoracoabdominal mobility as well as to assess possible associations of respiratory variables with clinical manifestations in women with FMS. The results show that the FMS group in this study has lower respiratory muscle endurance, inspiratory muscle strength and thoracic mobility compared to healthy participants. In addition, the study demonstrated that the lower inspiratory muscle strength, the greater the number of tender points and fatigue and lower axillary mobility. The Study II, entitled "Influence aerobic hydrotherapy program on lung function, respiratory muscle strength and thoracoabdominal mobility in women with fibromyalgia syndrome: a randomized controlled trial", aimed to evaluate the influence of an aerobic hydrotherapy program on respiratory variables and clinical manifestations in women with FMS and assess the association between respiratory variables and clinical manifestations. The results show that a 16-week aerobic hydrotherapy program increased the slow vital capacity, the forced vital capacity, the inspiratory muscle strength, the thoracic mobility, the pressure pain threshold, well-being, and decreased pain, and limitations caused by physical aspects. Clinical improvement was not associated with the respiratory variables. Conclusion: The subjects with FMS had lower respiratory muscle endurance, inspiratory muscle strength and thoracic mobility compared to healthy subjects. In addition, a 16-week aerobic hydrotherapy program showed to be effective in ameliorating lung function, inspiratory muscle strength, thoracic mobility, pressure pain threshold, well-being, pain and limitations caused by physical aspects. However, clinical improvement of FMS symptoms was not associated with the improvement of respiratory variables.